Fault location in an electrical energy distribution infrastructure with a wireless sensor network - Fortunato, Carlos (2013)
This article presents a detailed analysis of the applicability of wireless systems in the localization of faults in the energy distribution network. The hwardware and software architectures of the envised sensor solution will also be described and finally, the integration of this system into Smart Grids will be discussed in terms of automatic fault analysis. A pilot system has been tested in a subset of the Portuguese energy distribution infrastructure operated by EDP Energias de Portugal. It presents a new approach to a fault locator system for the power network. The purpose is to obtain faster and more reliable information about the disruptions in the power distribution network and their location. Furthermore, the wireless sensors allow remote detection of medium and low voltage (MV/LV) power transformer hotspots in order to identify emerging malfunction as well as detection of intrusion in the MV/LV power transformers.